Засоби вираження категорії локативності в романі Ліни Костенко "Маруся Чурай" - Нетребчук, Л.Н. (Культура народов Причерноморья, 2003)
Статья посвящена исследованию функционально-семантических особенностей категории локативности: определяется её статус и существующие языковые средства выражения; рассматриваются взаимосвязи с другими языковыми категориями; выявляется антропоцентрический характер локативов; анализируется реализация локативности в тексте. The article is devoted to the research of functional- semantic features of the category of locativity: the status of this category and existing linguistic means of expression are determined; interconnections with other linguistic categories are investigated; anthropocentric nature of locatives is revealed; the realization of locativity in the text is analysed.